Avaliação da atividade muscular mastigatória, nocicepção associada e participação do sistema endocanabinóide no comportamento bruxismo-símile em ratos - Silveira, Sarah Sanders (2015)
The increased masticatory muscle activity is considered a physical response to changes in emotional state. Stress and anxiety increase the myoelectric activity of the stomatognathic system muscles, with resulting parafunctions increase, as teeth clenching. Bruxism is a diurnal or nocturnal parafunctional activity including clenching or teeth grinding. Bruxism is strongly associated with the masticatory myofascial pain, a chronic facial pain of the masticatory muscles with possible blockage and limited mouth opening. The endocannabinoid system consists of cannabinoid receptors by the endogenous ligands (endocannabinoids) and proteins responsible for its metabolism. Endocannabinoids are involved in different physiological and pathological functions. The antinociceptive action of cannabinoids has been shown in several experimental models of pain, but there are no literature reports of cannabinoids involvement in nociception associated with muscle hyperactivity in parafunctional habits situations. The aim of this study was to study the masticatory muscle activity and nociception associated in emotional stress model in rats and the endocannabinoid system involvement. The study was approved by the Animal Research Ethics Committee of the Federal University of Ceará (N° 35/13). The communication box was used as stimulus instrument for emotional stress for 14 days. Subcutaneous electrodes were implanted in the masseter and temporal muscles region to evaluate the masticatory muscle activity and it was performed mechanical hyperalgesia test in these muscles during the emotional stress stimulation. Were also evaluated anxiety behavior parameters, body weight, adrenal glands gross weight and c-Fos expression and cannabinoid CB1 and CB2 receptors in the trigeminal ganglion and trigeminal spinal tract. Cannabinoid CB1 antagonist was administered and evaluated the nociceptive behavior. The expression of cannabinoid receptors in the masseter muscle was also assessed. The results showed a significant increase in stressed animals masticatory muscle activity on the seventh day of emotional stress stimulus. A significant reduction of masticatory muscles nociceptive threshold was observed, peaking on the eleventh day of emotional stress. The stressed animals showed anxiety behavior, with no differences in body weight or adrenal glands gross weight. The results also pointed that the stressed animals showed cytoplasmic vacuoles accumulation in the adrenal glands cortex, and increased expression of c-Fos and CB1 and CB2 receptors in the trigeminal ganglion and trigeminal spinal tract. The administration of the antagonist CB1 intensified the nociception on the fourth day of emotional stress. Cannabinoids CB1 and CB2 receptors have increased expression in the masseter muscle of the stressed animals. The data suggest that animals exposed to emotional stress have increased masticatory muscle activity and ‘brux-like’ behavior with a reduction in masticatory muscles nociceptive thresholds. Endocannabinoid system appears to be involved in the modulation of nociception induced emotional stress with increased expression of CB1 and CB2 receptors in the trigeminal ganglion, trigeminal spinal tract and masseter muscle.